A method for preparing self-dispersed triarylmethane nano lake pigment

By using cellulose nanocrystals and metal ions to collaborate the triarylmethane dyes, the problems of incomplete color-calcination, large particle size and poor sun resistance were solved, and nano-calcined pigments with excellent dispersion properties and high sun-fastness were prepared.

CN116462988BActive Publication Date: 2025-03-28JIANGNAN UNIV +1

Patent Information

Application Number
CN202310220523.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-03-28
Estimated Expiration
2043-03-07

AI Technical Summary

Technical Problem

The triarylmethane colored pigment has incomplete precipitation during the colored capping process, large crystal particle size, high control requirements for system pH, and poor sun-resistant color fastness, which limits its application field.

Method used

Cellulose nanocrystals (CNC) are used as dispersant, and the triarylmethane dyes are color-capping with metal ions. The dye is fixed on the surface of the CNC through the bridging of metal ions to prepare nanoscale color-capping pigments.

Benefits of technology

The completeness of the chromatinization process, uniformity of crystal particle size and sun-resistant fastness are achieved, reducing production costs and expanding the application field of pigments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004116423300000071
    Figure BDA0004116423300000071
  • Figure BDA0004116423300000081
    Figure BDA0004116423300000081
Patent Text Reader

Abstract

The invention discloses a method for preparing a self-dispersible triarylmethane nano-lake pigment, which comprises the following steps: S1, dispersing cellulose nanocrystals in deionized water, dissolving triarylmethane dyes in water, and preparing a metal salt solution; S2, uniformly mixing and stirring the three; S3, obtaining a lake pigment after centrifugal separation or filtration; S4, dispersing the lake pigment in step S3 in water to obtain a high-concentration dispersed pigment or drying to obtain a pigment powder. The invention adopts cellulose nanocrystals as a dispersant, and cooperates with metal ions to lake the triarylmethane dyes, and the obtained precipitate particle size is at the nanometer scale and has excellent self-dispersibility in water, so that the light fastness of the lake pigment can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lake pigment production, in particular to a method for preparing self-dispersed triarylmethane nano lake pigment. Background Art

[0002] Triarylmethane lake pigments are characterized by bright colors and high tinting power, and are widely used in the coloring of inks, plastics, cosmetics, and paint pastes. This type of pigment is usually prepared by combining triarylmethane dyes with heteropolyacid precipitants under acidic conditions, and obtaining triphenylmethane phosphotungstomolybdate crystals after sedimentation. The finished pigment is then subjected to ultrafine dispersion treatment. For example, CN 102863818 uses a heteropolyacid composed of sodium tungstate, sodium molybdate, and sodium dihydrogen phosphate as a precipitant to lake basic violet to produce a pigment suspension, and further adds a high-efficiency dispersant to post-treat the pigment to reduce the pigment particle size and improve its dispersibility; CN113480874 also uses a heteropolyacid composed of sodium tungstate, sodium molybdate, and sodium dihydrogen phosphate as a precipitant to lake water-soluble dyes, and introduces a pigment additive into the mixed system to improve the dispersibility of the lake pigment. However, the use of inorganic heteropolyacids as precipitants has the common problems of incomplete lake formation, large crystal size, and extremely high requirements for system pH control. In addition, the demethylation of the parent molecule of triarylmethane dyes and the photooxidative cleavage of the central C-phenyl bond after exposure to light easily destroy the color system, resulting in poor sunlight fastness of such pigments, which greatly limits the application of such dyes. Current technology mainly improves the sunlight fastness of pigments by methods such as doping ultraviolet absorbers into finished pigments. For example, CN101955689 uses sulfonic acids or carboxylic acids with aromatic groups to mix and grind triarylmethane lake pigments to improve the light fastness and sunlight resistance of the pigments. However, the compatibility of such blended pigments with auxiliary agents is poor, and their sunlight resistance cannot be maintained for a long time. Most triarylmethane lake pigments prepared based on the inorganic heteropolyacid precipitation method have large particle size, require ultrafine dispersion treatment, and have poor sunlight fastness. Summary of the Invention

[0003] The present invention provides a method for preparing self-dispersible triarylmethane nano-lake pigments. Cellulose nanocrystals (CNC) are used as a dispersant, and metal ions are used to lake the triarylmethane dyes. The resulting precipitate has a nanometer-scale particle size and excellent self-dispersibility in water, thereby improving the light fastness of the lake pigment.

[0004] To this end, the present invention provides a method for preparing a self-dispersed triarylmethane nano-lake pigment, characterized in that it comprises the following steps:

[0005] S1. Dispersing cellulose nanocrystals in deionized water, dissolving triarylmethane dye in water, and preparing a metal salt solution;

[0006] S2, mix the three evenly and stir;

[0007] S3, obtaining lake pigment after centrifugal separation or filtration;

[0008] S4, dispersing the lake pigment in step S3 in water to obtain a high-concentration dispersed pigment or drying it to obtain pigment powder.

[0009] As a further description of the above technical solution:

[0010] In step S1, the Zeta potential of the cellulose nanocrystals is -10mV to -50mV, the length of the cellulose nanocrystals is 50nm to 300nm, and the surface functional groups of the cellulose nanocrystals are sulfonate groups, carboxyl groups, and phosphate groups.

[0011] As a further description of the above technical solution:

[0012] In step S1, the concentration of cellulose nanocrystals is 0.01 wt.% to 4.0 wt.%.

[0013] As a further description of the above technical solution:

[0014] In step S1, the concentration of the triarylmethane dye is 0.01 wt.% to 1.0 wt.%.

[0015] As a further description of the above technical solution:

[0016] In step S1, the metal salt is one or more of copper salt, calcium salt, magnesium salt, zinc salt, chromium salt, etc.

[0017] As a further description of the above technical solution:

[0018] In step S1, the concentration of the metal salt is 0.001 wt.% to 2.0 wt.%.

[0019] As a further description of the above technical solution:

[0020] In step S2, the molar ratio of cellulose nanocrystals: metal ions: dye is 1: (0.1-2): (0.1-2).

[0021] As a further description of the above technical solution:

[0022] In step S2, the mixing method is one or more of magnetic stirring and ultrasonic stirring, and the stirring time is 10 minutes to 120 minutes.

[0023] As a further description of the above technical solution:

[0024] In step S3, the centrifugal speed is 3000 r / min to 10000 r / min.

[0025] As a further description of the above technical solution:

[0026] In step S4, the drying method is spray drying or freeze drying, and the concentration of the pigment dispersion is 1.0 wt.% to 10 wt.%.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] The present invention uses cellulose nanocrystals (CNC) as an anchoring template in the process of laking triarylmethane dyes, and utilizes the bridging effect of metal ions to effectively fix them on the CNC. Thanks to the good dispersion stability of CNC itself, a nano-lake pigment with self-dispersibility is prepared. The directional linkage of metal ions during the laking process further restricts the crystallization growth direction of the triarylmethane lake pigment crystals on the CNC template, making it easier to obtain a nano-lake pigment with uniform morphology and structure, and promoting a more stable crystal structure, thereby improving the light fastness of the nano-lake pigment.

[0029] The nano-lake pigment preparation method of the present invention has a complete lake process, uniform crystal particle size distribution, simple process, good self-dispersion performance and stable crystal structure, which reduces subsequent production and processing costs and effectively improves the sunlight fastness of the pigment, thereby effectively expanding the practical application field of the nano-lake pigment. DETAILED DESCRIPTION

[0030] The following describes exemplary embodiments of the present disclosure in more detail. Although exemplary embodiments of the present disclosure are shown, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. Instead, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0031] The test method is analyzed in detail as follows:

[0032] (1) Size and particle size distribution:

[0033] The pigment particle size and particle size distribution (PDI) of the dispersions in Examples 1 to 3 and Comparative Example 1 were analyzed and characterized using a laser particle size analyzer.

[0034] (2) Light fastness:

[0035] According to GB / T 8427-2019 “Textiles—Tests for Color Fastness—Color Fastness to Artificial Light: Xenon Arc Fading Light”, the printed fabrics of Examples 1 to 3 and Comparative Example 1 were tested and rated for sunlight fastness using a sunlight fastness meter, with grade 8 being the best and grade 1 being the worst.

[0036] Example 1:

[0037] A method for preparing a self-dispersed triarylmethane nano-lake pigment, comprising the following steps:

[0038] (1) Preparation of cellulose nanocrystal (CNC) dispersion: 0.5 g of CNC was dispersed in 49.5 g of deionized water to prepare a CNC dispersion with a mass concentration of 1 wt.%;

[0039] (2) Preparation of dye solution: 0.5 g of triarylmethane dye was dissolved in 49.5 g of deionized water to prepare a dye solution with a mass concentration of 1 wt.%;

[0040] (3) Preparation of metal salt solution: 0.5 g of metal salt was dissolved in 49.5 g of deionized water to prepare a metal salt solution with a mass concentration of 1 wt.%;

[0041] (4) The solutions in steps (1), (2), and (3) were placed in a beaker and magnetically stirred at room temperature for 60 min at a stirring speed of 500 rpm / min;

[0042] (5) After the reaction is completed, the mixed solution in step (4) is centrifuged at 8000 r / min, washed with alcohol, and washed with water to obtain nano lake pigment ①, which is then freeze-dried for 48 hours;

[0043] (6) 0.005 g of the nano lake pigment prepared in step (5) was ultrasonically dispersed in 20 ml of deionized water to obtain pigment dispersion Example 1;

[0044] (7) 0.2 g of the above-mentioned nano lake pigment ① was dispersed in 15 ml of water, 10 g of adhesive and 1 g of thickener were added to obtain a printing paste, which was scraped onto a standard polyester interlining cloth through a silk screen and then pre-baked and baked to obtain printed fabric Example 1.

[0045] Example 2:

[0046] A method for preparing a self-dispersed triarylmethane nano-lake pigment, comprising the following steps:

[0047] (1) Preparation of cellulose nanocrystal (CNC) dispersion: 0.5 g of CNC was dispersed in 49.5 g of deionized water to prepare a CNC dispersion with a mass concentration of 1 wt.%;

[0048] (2) Preparation of dye solution: 1 g of triarylmethane dye was dissolved in 49.5 g of deionized water to prepare a dye solution with a mass concentration of 2 wt.%;

[0049] (3) Preparation of metal salt solution: 0.5 g of metal salt was dissolved in 49.5 g of deionized water to prepare a metal salt solution with a mass concentration of 1 wt.%;

[0050] (4) The solutions in steps (1), (2), and (3) were placed in a beaker and magnetically stirred at room temperature for 60 min at a stirring speed of 500 rpm / min;

[0051] (5) After the reaction is completed, the mixed solution in step (4) is centrifuged at 8000 r / min, washed with alcohol, and washed with water to obtain nano lake pigment ②, which is then freeze-dried for 48 hours;

[0052] (6) 0.005 g of the nano lake pigment prepared in step (5) was ultrasonically dispersed in 20 ml of deionized water to obtain pigment dispersion Example 2;

[0053] (7) 0.2 g of the above-mentioned nano lake pigment ① was dispersed in 15 ml of water, 10 g of adhesive and 1 g of thickener were added to obtain a printing paste, which was scraped onto a standard polyester interlining cloth through a silk screen and then pre-baked and baked to obtain printed fabric Example 2.

[0054] Example 3:

[0055] A method for preparing a self-dispersed triarylmethane nano-lake pigment, comprising the following steps:

[0056] (1) Preparation of cellulose nanocrystal (CNC) dispersion: 0.5 g of CNC was dispersed in 49.5 g of deionized water to prepare a CNC dispersion with a mass concentration of 1 wt.%;

[0057] (2) Preparation of dye solution: 0.5 g of triarylmethane dye was dissolved in 49.5 g of deionized water to prepare a dye solution with a mass concentration of 1 wt.%;

[0058] (3) Preparation of metal salt solution: 1 g of metal salt was dissolved in 49.5 g of deionized water to prepare a metal salt solution with a mass concentration of 2 wt.%;

[0059] (4) The solutions in steps (1), (2), and (3) were placed in a beaker and magnetically stirred at room temperature for 60 min at a stirring speed of 500 rpm / min;

[0060] (5) After the reaction is completed, the mixed solution in step (4) is centrifuged at 8000 r / min, washed with alcohol, and washed with water to obtain nano lake pigment ③, which is then freeze-dried for 48 hours;

[0061] (6) 0.005 g of the nano lake pigment prepared in step (5) was ultrasonically dispersed in 20 ml of deionized water to obtain pigment dispersion Example 3;

[0062] (7) 0.2 g of the above-mentioned nano lake pigment ① was dispersed in 15 ml of water, 10 g of adhesive and 1 g of thickener were added to obtain a printing paste, which was scraped onto a standard polyester interlining cloth through a silk screen and then pre-baked and baked to obtain printed fabric Example 3.

[0063] Comparative Example 1:

[0064] (1) 0.005 g of commercially available triarylmethane lake pigment was dispersed in deionized water for 20 min to obtain a pigment dispersion of comparative example 1;

[0065] (2) 0.2 g of commercially available triarylmethane lake pigment was dispersed in 15 ml of water, 10 g of adhesive and 1 g of thickener were added to obtain a printing paste, which was scraped onto a standard polyester interlining fabric through a silk screen and then pre-baked and baked to obtain a printed fabric control example 1.

[0066] Table 1 Dispersibility and light fastness of samples

[0067] sample Particle size / nm PDI Light fastness Example 1 255.4 0.201 4~5 Example 2 187.6 0.145 5 Example 3 152.1 0.127 5 Comparative Example 1 759.8 0.856 3

[0068] Comparative Example 2:

[0069] 0.2 g of commercially available triarylmethane lake pigment was dispersed in 15 ml of water, 10 g of adhesive and 1 g of thickener as well as ultraviolet absorbers UV400, UV531 and UV1577 at different concentrations were added to obtain a printing paste, which was then scraped onto a standard polyester interlining cloth through a silk screen using a scraper, and then pre-baked and baked to obtain printed fabric control example 2.

[0070] Table 2 Light fastness of comparative example 2

[0071]

[0072]

[0073] The present invention discloses a method for preparing self-dispersible triarylmethane nano-lake pigments, which belongs to the technical field of lake pigment production. The lake pigment preparation method provided by the present invention enables dye molecules to be fixed on the surface of cellulose nanocrystals with the help of the linking effect of metal ions, thereby obtaining a self-dispersible nano-lake pigment with uniform morphology and stable crystal structure, and the light fastness is greatly improved. The particle size of this type of lake pigment is significantly reduced compared to ordinary commercial pigments, the distribution state is also more concentrated, and it has good self-dispersion performance. Compared with pure commercial and pigment-printed fabrics with added ultraviolet absorbers, the light fastness of this type of nano-lake pigment is greatly improved, from the original level 3 to about level 5. The nano-lake pigment prepared by the present invention has excellent dispersibility, uniform particle size distribution, good light fastness, and has broad application prospects in inks, inkjet printing, and coating paste coloring.

[0074] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A method for preparing a self-dispersible triarylmethane nano lake pigment, characterized in that: The following steps are involved: S1, dispersing cellulose nanocrystals in deionized water, dissolving triarylmethane dye in water, and preparing a metal salt solution; S2, mix the three evenly and stir; S3, obtaining lake pigment after centrifugal separation or filtration; S4, the step S3 lake pigment dispersed in water to obtain a high concentration of dispersed pigment or dried pigment powder; In the step S1, the Zeta potential of the cellulose nanocrystals is -10 mV to -50 mV, the length of the cellulose nanocrystals is 50 nm to 300 nm, the surface functional groups of the cellulose nanocrystals are sulfonate groups, carboxyl groups, and phosphate groups, and in the step S2, the molar ratio of cellulose nanocrystals: metal ions: triarylmethane dyes is 1: (0.1-2): (0.1-2).

2. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S1, the concentration of cellulose nanocrystals is 0.01 wt.% to 4.0 wt.%.

3. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S1, the concentration of the triarylmethane dye is 0.01 wt.% to 1.0 wt.%.

4. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S1, the metal salt is one or more of copper salt, calcium salt, magnesium salt, zinc salt and chromium salt.

5. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S1, the concentration of the metal salt is 0.001 wt.% to 2.0 wt.%.

6. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S2, the mixing method is one or more of magnetic stirring and ultrasonic stirring, and the stirring time is 10 min to 120 min.

7. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S3, the centrifugal speed is 3000 r / min to 10000 r / min.

8. The method for preparing a self-dispersible triarylmethane nano lake pigment according to claim 1, characterized in that: In step S4, the drying method is spray drying or freeze drying, and the concentration of the pigment dispersion is 1.0 wt.% to 10 wt.%.

Citation Information

Patent Citations

  • Microparticles of cellulose nanocrystals with pigment nanoparticles bound thereto and method of production thereof

    US20220040053A1

Cited By

  • Natural dye lake pigment and preparation method thereof

    CN120904709A